Peculiarities of English-teaching practice for students of electrical engineering - Ponikarovska, Svitlana; Понікаровська, Світлана Володимирівна (Харківський національний автомобільно-дорожній університет, 2021)
As engineering is a vast area of study in the world and English is a recognized language of international communication, knowledge of English is compulsory. Besides, we live in the digital age and English is the only language in latest version applications, installation guides and software instructions. Learning for students of engineering from not English-speaking countries is very important not only for their scholastic life, but also for their prospective career, mobility and successful communication. Goal. The goal of the work is to determine the features of teaching English to the students of electrical engineering, specify the role of English language for engineering students, outline the technique and methods of organizing the teaching process, look into innovative technologies of teaching. Methodology. The methodology is based on the analysis of the existing methods of teaching which are many, comparison of classical and innovative methods and analysis of the strategies of different methods. The paper emphasizes creative approach in teaching as a key to success. Results. The work provides a brief theoretical grounding and a working definition for creativity and motivation in teaching English for Specific Purposes and English as a Foreign language. It also explores the role and function of creativity in the context of the changing paradigm regarding the overall scope of the educational system in general and of the language learning in particular. Originality. The work offers combining creative methods and active strategies in fostering better language acquisition during English classes. When we see that the students are involved and motivated, it means that the strategy works. The teacher-oriented method is not currently welcomed in language teaching, and the ways to make it student-oriented are offered in the work. Practical value. The paper contains some practical advice on how a teacher can create more situations in which students can contribute, initiate, control and create. Keeping in mind the dependence of the learning success on creativity of teachers and motivation of students, new innovative methods of teaching in proper combination with theory of language can be used.
Особливості практики викладання англійської мови студентам електротехнічної спеціальності
Keywords: creativity; engineering students; communicative; competence; learning success; творчість; студенти інженерних спеціальностей; комунікативний; компетенція; успіх навчання; 378.14; 10.30977/VEIT.2021.20.0.08